Uterine fibroids are associated with increased risk of pre-eclampsia: A case-control study - Gong, Lina; Liu, Meng; Shi, Haiheng; Huang, Ying (Frontiers in Cardiovascular Medicine, 2022)
Purpose Uterine fibroids are associated with hypertension in non-pregnant women. We aimed to evaluate the association between uterine fibroids and pre-eclampsia (PE). Patients and methods Participants were pregnant women who delivered in the Department of Obstetrics of the People's Hospital of Xinjiang Uygur Autonomous Region between January and December 2021. Patients with PE were identified as the case group, whereas those without PE were selected as the control group, using age-matching and a ratio of 1:5. Ultrasound examination during early pregnancy was used to detect uterine fibroids. Multivariable logistic regression was applied to evaluate the association between uterine fibroids and PE. Results In total, 121 cases with PE and 578 controls without PE were included, with mean age of 32.9 years and gestational age of 37.7 weeks. Time of ultrasound examination was 12.0 ± 2.6 weeks. The case group had a significantly higher exposure rate of uterine fibroids than the control group (14.0 vs. 6.9%, P = 0.009). Multivariable Logistic regression models adjusted for potential confounding factors, including gestational age and blood pressure in early gestation, showed that pregnant women with uterine fibroids in early pregnancy exhibited three-fold higher odds for PE (OR, 3.02; 95% CI, 1.20–7.60; P = 0.019). Sensitivity analysis, which excluded those with gestational diabetes, further confirmed the robustness of the results. The association between uterine fibroids and PE was stronger in pregnant women aged ≥35 years and multiparas. Conclusion Uterine fibroids are significantly associated with an increased risk of PE in pregnant women. Uterine fibroids may serve as a new factor for identifying pregnant women at high risk of PE, and the effect of myomectomy before pregnancy on prevention of PE is worth further exploring.